A History of Radionuclide Studies in the UK: 50th Anniversary of the British Nuclear Medicine Society - McCready, Ralph; Gnanasegaran, Gopinath; Bomanji, Jamshed B.; McCready, Ralph; Gnanasegaran, Gopinath; Bomanji, Jamshed B. (Cham Springer Nature, 2016)
nuclear medicine; history of medicine
English
Keywords: Medical equipment & techniques; nuclear medicine; history of medicine